2019
DOI: 10.1002/bies.201800201
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Excision Repair and Transcription‐Associated Genome Instability

Abstract: Transcription is a potential threat to genome integrity, and transcription‐associated DNA damage must be repaired for proper messenger RNA (mRNA) synthesis and for cells to transmit their genome intact into progeny. For a wide range of structurally diverse DNA lesions, cells employ the highly conserved nucleotide excision repair (NER) pathway to restore their genome back to its native form. Recent evidence suggests that NER factors function, in addition to the canonical DNA repair mechanism, in processes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 135 publications
(198 reference statements)
1
25
0
Order By: Relevance
“…Most research targets are directly related to chromosomal machineries, including DNA replication/repair, chromatin condensation, condensed chromosome segregation, and regulators of cell cycle checking points. Traditionally, for example, gene mutations responsible for chromosome instability syndromes and drugs that can directly interfere with chromosomal machineries were frequently under investigation [ 38 , 39 , 40 , 41 ].…”
Section: Stress As a Hidden Link: All Roads Lead To Cinmentioning
confidence: 99%
“…Most research targets are directly related to chromosomal machineries, including DNA replication/repair, chromatin condensation, condensed chromosome segregation, and regulators of cell cycle checking points. Traditionally, for example, gene mutations responsible for chromosome instability syndromes and drugs that can directly interfere with chromosomal machineries were frequently under investigation [ 38 , 39 , 40 , 41 ].…”
Section: Stress As a Hidden Link: All Roads Lead To Cinmentioning
confidence: 99%
“…Pulldown experiments in nuclear extracts of bXPF and control BirA MEFs confirmed that the endogenous bXPF interacts with the TATA-associated factors (TAFs) TAF4, TAF6, and TAF10 of the TFIID complex (Kamileri et al, 2012c) as well as with CTCF and the cohesin subunits SMC1A and SMC3 ( Figure 5A and Figure 5B ) (Chatzinikolaou et al, 2017) highlighting the possible role of ERCC1-XPF complex in transcription initiation and chromatin looping (Apostolou et al, 2019; Kamileri et al, 2012a). Moreover, these findings along with the preferential recruitment of bXPF on promoters upon transcription stimulation ( Figure 2B-C ) and the identification of several topoisomerases in the 607 bXPF-bound core proteome ( Figure 4G ) fit well with the known involvement of ERCC1-XPF in DNA DSB repair (Ahmad et al, 2008; Li et al, 2019).…”
Section: Resultsmentioning
confidence: 90%
“…We previously showed that ERCC1-XPF engages together with RNAPII and the basal transcription machinery at the promoters of growth genes during postnatal hepatic development (Apostolou et al, 2019; Kamileri et al, 2012a; Kamileri et al, 2012b). However, the structure-specific requirement of ERCC1-XPF for incision made it difficult to justify the functional role of the endonuclease complex on promoters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inborn defects in RNA processing or DNA repair associate with progeria [53][54][55] , the metabolic syndrome [56][57][58] , neurodegeneration [59][60][61][62] and cancer [63][64][65][66][67] , arguing for functional links between genome maintenance and the splicing machinery in development or disease. Using an in vivo biotinylation tagging approach in mice, we nd that XAB2 interacts with components of the core spliceosome as well as with DDB1 involved in UV-induced DNA damage recognition and XPA that plays a prominent role in the assembly of the NER incision complex at sites of DNA damage 62,68 . As DDB1 is successfully recruited to UV-induced CPDs in siXab2 cells, the implication of XAB2:DDB1 interaction remains elusive.…”
Section: Discussionmentioning
confidence: 99%